HxMoO3@C nanobelts: Green synthesis and superior lithium storage properties. (9th March 2015) - Song, Yeping; Wang, Hai; Li, Zihua; Ye, Naiqing; Wang, Linjiang; Liu, Yong
Abstract: MoO3 could be a promising high capacity anode material for lithium ion batteries (LIBs). However, its applications have been hindered by its poor electronic conductivity. To address these issues, in this work, Hx MoO3 @C nanobelts were synthesized by mild hydrothermal treatment of precursor MoO3 nanobelts only with the assistance of glucose and ethanol. Subsequently, a catalysis-insertion model was proposed to describe the formation of Hx MoO3 nanobelts. When tested as LIBs anodes, the superior reversible capacities of LIBs anodes were realized from Hx MoO3 @C nanobelts. The Hx MoO3 @C nanobelts electrode exhibited superior reversible capacity of 480 mAh g −1 retained at 200 mA g −1 after 100 cycles, and a superior rate capacity of 337 mAh g −1 retained after 100 cycles at 500 mA g −1 . The superior performance achieved in Hx MoO3 @C nanobelts anode system are attributed to the synergistic effect of the conductive Hx MoO3, the enlargement of interplanar spacing and uniform carbon coating shell. Graphical abstract: Highlights: The Hx MoO3 @C nanobelts are synthesized via green reduction-insertion method for the first time. The electrochemical behavior of Hx MoO3 @C nanobelt is investigated. Carbon coating and hydrogen insertion are achieved simultaneously. The Hx MoO3 @C nanobelts anode material shows good electrochemical properties.